Assessment of water demand from urban and rural area in Kota Bharu, Kelantan - Fauzi, Siti Nur Farzilah; Musa, Sabariah (Penerbit UTHM, 2022)
Population growth and inefficient water supply management are the main factors that cause treated water supply to not function properly. This problem has been faced in the state of Kelantan for many years and until now this problem is still faced by the local community, especially in the district of Kota Bharu. Therefore, this study was conducted to identify the rate of water demand from urban and rural areas and the cost-effective of water distributed in Kota Bharu, Kelantan. A total of 50 respondents provided feedback through this survey questionnaire. The results showed that a large number of residents from urban areas use treated water (100 %) provided by Air Kelantan Sendiri Berhad (AKSB) while rural areas still use treated water (62